PERLINDUNGAN TERHADAP PASIEN PADA RUMAH SAKIT DIRGAHAYU MENURUT UU KESEHATAN NO. 36 TAHUN 2009 - Yuniwa Yuniwa (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
Abstract According to a general explanation of Law No. 36/2009 development of the health sector is one of the efforts in national development is expected to create a condition of the people who have awareness, safety and ability to live a healthy life so as to realize an optimal health status, health development, are intimately associated with good resources in the form of facilities and infrastructure and the development of health measures that are not only focused on healing as before, but also includes efforts to improve health, disease prevention and health recovery. Basically every patient who had been disadvantaged by the doctor may demand compensation to a doctor is concerned, if the doctor concerned is proved to have made a mistake or negligence in performing their duties which those rights have been set in UU.No.23 / 92 Article 55 paragraph 1 and the hospital as a manager and the party responsible for the mistakes of his subordinates (1367 Civil Code), as long as this demand ever undertaken by the patient to the hospital or to the doctor in question, in the form of demands restoration of the original state and no one demands to on the court.